2020
DOI: 10.1177/1354856520970141
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the entertainment ecosystem of Wattpad: Platforms, publishing and adaptation

Abstract: Digital platforms have reshaped the creative industries and restructured relationships between media sectors. Creative writing and reading social media platforms like Wattpad are challenging what it means to publish fiction in the early 21st century, and digital streaming platforms like Netflix, Hulu and others have begun looking to these platforms to source creative content for adaptation. Praxis on creative writing social media platforms is shaped by a complex and ongoing interplay between the technocultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Our case studies show that prizes, especially for unpublished work, remain important sources for the accumulation of symbolic capital, which is important in and transferable across both models of capitalism. Intensified connections between traditional and digital media products can also be seen in media and technology companies that trade in the commercialisation of intellectual property through adaptations and transmedia ecosystems, such as Wattpad, Webtoon and Tencent (Parnell, 2021a). Rather than being independent and competing modes of capitalism, conglomerate capitalism and digital platform capitalism are closely interwoven, as the discovery of these debut successes shows.…”
Section: Truth Emotion and The Interplay Of Capitalist Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our case studies show that prizes, especially for unpublished work, remain important sources for the accumulation of symbolic capital, which is important in and transferable across both models of capitalism. Intensified connections between traditional and digital media products can also be seen in media and technology companies that trade in the commercialisation of intellectual property through adaptations and transmedia ecosystems, such as Wattpad, Webtoon and Tencent (Parnell, 2021a). Rather than being independent and competing modes of capitalism, conglomerate capitalism and digital platform capitalism are closely interwoven, as the discovery of these debut successes shows.…”
Section: Truth Emotion and The Interplay Of Capitalist Modesmentioning
confidence: 99%
“…Publishing studies is attentive to the new economics of the book industry, including the rise of technology companies following the extensive digitisation of the industry (Parnell, 2021a; Ray Murray and Squires, 2013; Thompson, 2012). An important component of these debates is the power relations that shape a globalised industry (Casanova, 2004; Sapiro, 2010).…”
Section: Publishing Bestsellers and Capitalismmentioning
confidence: 99%
See 1 more Smart Citation
“…POET, AUTHOR, PRODUCER, CREATOR In The Death of the Artist: How Creators are Struggling to Survive in the Age of Billionaires and Big Tech, essayist and literary critic William Deresiewicz presents a well-researched argument for how we are now progressing with great speed into a fourth paradigm for the artist: the artist as producer (Deresiewicz 2020). This is supported by research done on artists' relation to social media and the internet (Marshall, Moore, & Barbour 2019;Marwick 2015;Parnell 2021;van Driel & Dumitrica 2021). Research related to the literary industry also points to two co-existing modes of capitalism making up the literary field: conglomerate capitalism and platform capitalism (Parnell & Driscoll 2021: 1).…”
mentioning
confidence: 77%
“…1While crowdfunding and the presence of multiple communities dedicated to digital fiction still retain a strong democratic valence, with its popularity heavily relying on the dedications of its users and writers, the case of Wattpad has become more problematic in this respect. A recent study by Parnell (2021) showed that heterogeneity and egalitarianism (proudly stated in Wattpad’s Code of Conduct), are not guaranteed by the platform’s relatively open system of publishing. Partnerships with external (Hulu and Netflix) and platform-specific forms of capital (Wattpad Premium and Wattpad Stars) significantly changed the platform since its launch.…”
mentioning
confidence: 99%